Primary Pineal Rhabdomyosarcoma: A Rare Case - Vaidya, Mihir Mohan (Asian J Neurosurg, 2019)
Primary pineal rhabdomyosarcoma (RMS) is extremely rare, and only three cases have been reported so far. Here, we report a case of 12-year-old male who presented with complaints of diplopia and diminution of vision since 15 days. He also had left-sided facial paresis. Magnetic resonance imaging brain revealed a space-occupying lesion in the region of pineal gland. The patient underwent midline suboccipital craniectomy with excision of tumor. Microscopic examination revealed a highly cellular tumor with areas showing small round cells admixed with cells having abundant eosinophilic cytoplasm resembling rhabdomyoblasts and multinucleated giant cells. Differential diagnoses of pineal anlage tumor and primary RMS were considered. The tumor cells were positive for desmin while being negative for synaptophysin and glial fibrillary acidic protein. Myogenin was used to confirm the diagnosis of RMS, which showed focal nuclear positivity. INI1 was retained. All the markers for germ cell tumors were negative.